Contos de Grimm (1812-1815) : dos significantes na representação da verossimilhança artístico-literária ou aristotélica - Almeida, Lícia Cristina Dalcin de (2016)
This reading is developed from the idea of classical, artistic and literary or Aristotelian verisimilitude as “psychological verisimilitude”, in other words, a verisimilitude which depends on contrasts between receiver’s signifiers and literary work’s signifiers. Thus, this verisimilitude promotes a “feeling of truth” that reproduces, in the receiver, actual sensations experienced on the real world. The signifier’s concept that guides this approach is from Lacan’s theories. “Truth” or “real world” in this reading depend on theoretical lines which are oriented to representation and language, as Kant, Nietzsche, Freud, Lacan himself, Wittgenstein and other researchers, especially readers of those listed. Aristotle is the verisimilitude’s theoretician - and he linked it to “actions of high importance” which are dependants on “necessity”. To the concept of “necessity” we associate the desire from Lacanian psychoanalytic line, which sets the sequence of signifiers applications operated under the command of a subject. That way, we point out in signifiers from Grimm tales (the first edition) verisimilar and also nonverisimilar actions. We also show traits that may refer to the viability of a concept for a “grimmismo” or aesthetics that have guided the two brothers’ tales writing.